Urine Nitric Oxide Is Lower in Parents of Autistic Children - Yao, Lulu; Cai, Kun; Mei, Fanghua; Wang, Xiaohua; Fan, Chuangang; Jiang, Hong; Xie, Fang; Li, Ying; Bai, Lu; Peng, Kang; Deng, Wenwen; Lai, Shenghan; et al. (Frontiers in Psychiatry, 2021)
Parents raising children with autism spectrum disorder (ASD) usually carry on their daily life under tremendous stress, but rare research sources had been devoted to this population. It is known that parents’ health status directly impacts therapeutic outcome of ASD children. As an important regulator in cardiovascular, nervous and immune systems, nitric oxide (NO) level hasn’t been reported in parents of ASD children yet. In this study, we quantitated urine nitrite and nitrate from 43 ASD parents (ASD-P), and 43 healthy adults in the same range of age (Control) who didn’t have any ASD descendants. Comparison between the ASD-P and Control groups showed that NO2-, NO3- and NO2- /NO3- were all significantly lower in the ASD-P group. Analysis on the interaction effect of gender and group indicated that urine NO3- of mothers in ASD-P was much lower than that in females of the Control group, but no significant difference was observed between males in both groups. It is for the first time that urine NOx levels were reported to differentiate parents of autistic children from other adults without ASD descendants, which was even more notable between female participants. This phenomenon suggests that mothers of autistic children might had experienced more mental and physical stressors, which led to decreased NO levels during metabolism. Further investigations are necessary to uncover the etiology of low urine NO among parents of autistic children.